High-brightness laser imaging with tunable speckle reduction enabled by electroactive micro-optic diffusers - Farrokhi, Hamid (2018)
High coherence of lasers is desirable in high-speed, high-resolution, and wide-field imaging. However, it also causes unavoidable background speckle noise thus degrades the image quality in traditional microscopy and more significantly in interferometric quantitative phase imaging (QPI). QPI utilizes optical interference for high-precision measurement of the optical properties where the speckle can severely distort the information. To overcome this, we demonstrated a light source system having a wide tunability in the spatial coherence over 43% by controlling the illumination angle, scatterer’s size, and the rotational speed of an electroactive-polymer rotational micro-optic diffuser. Spatially random phase modulation was implemented for the lower speckle imaging with over a 50% speckle reduction without a significant degradation in the temporal coherence. Our coherence control technique will provide a unique solution for a low-speckle, full-field, and coherent imaging in optically scattering media in the fields of healthcare sciences, material sciences and high-precision engineering.